Quality control of SIRGAS ZTD products - Mackern Oberti, María Virginia (2022)
The SIRGAS-CON network currently has more than 450 continuous GNSS stations, and it is used for geodetic purposes. In atmospheric studies, it is used for ionospheric monitoring and for the estimation of zenith tropospheric delays (ZTDs). From the Neutral Atmosphere Analysis Center of SIRGAS, Centro de Ingeniería Mendoza Argentina, the final tropospheric products of this network are generated after several stages of quality controls and filtering, in order to be published on a daily basis in the official website of SIRGAS, since 2014 (https://sirgas.ipgh.org/en/products/tropospheric-delays). These products arise from adjusting the solutions estimated by different SIRGAS analysis centers. Prior to the combination, a quality control of the individual solutions is carried out, based on the precision estimator of each parameter and an internal control of each solution with respect to the combined value. In this work, we show the quality control process of the inputs, the selected tolerance and its justification. The internal consistency analysis of tropospheric parameters for a period of 7 years was carried out. We also exposed the improvements in the estimation of tropospheric parameters implemented during 2021 and its impact in the generation of the final ZTD products (in 99% of the stations the mean standard deviation of ZTD is less than 1 mm).